Ricky ricotta's mighty robot vs. the naughty nightcrawlers from neptune ebook - Pilkey, Dav (Ricky Ricotta, 2016)
From Dav Pilkey, the worldwide bestselling author-illustrator of Dog Man, and award-winning illustrator Dan Santat comes an out-of-this-world friendship adventure in full color! Ricky Ricotta and his Mighty Robot are in for a sticky, slimy surprise! Ricky and his Mighty Robot have built the coolest fort Squeakyville has ever seen, and they can't wait for the fun to begin! But then Cousin Lucy arrives with her pets and plans to turn it into a princess castle — what a party pooper! Things completely fall apart when Nimrod Nightcrawler, a wicked worm from the planet Neptune, digs a tunnel under Ricky's fort, trapping the Mighty Robot. Now it's up to Ricky and Lucy to put a stop to this nightmare — and save their friend!